Linguoculturological Analysis of Proverbs and Sayings in the Russian and Uzbek Languages - Mustafoyeva Lobar Maxmutovna (International Journal on Integrated Education, 2022)
Linguoculturology focuses primarily on the content side of proverbs and sayings, and in this regard, it uses data from other humanities. The article presents a comparative analysis of proverbs expressing the specific characteristics of Russian and Uzbek linguistic cultures. Russian proverbs and sayings containing the names of food products are used as a source of material for the dictionary "Proverbs and Sayings of the Russian people" by V.I. Dahl. The analysis of proverbs and sayings of the Russian language contained in V.I. Dahl's dictionary, as well as their comparison with Uzbek proverbs and sayings, allows us to supplement with new details the worldview that has developed between the two peoples and has been consolidated in the language.